(untitled) (Dhaka University Journal of Biological Sciences, 2024)
Shrimps are among the most intriguing groups within the Decapoda order. In Bangladesh, penaeid shrimps hold significant economic value as a major export commodity. This study aimed to analyze the morphometric and molecular characteristics of penaeid shrimps in Bangladesh. Two species of penaeid shrimp, Penaeus pulchricaudatus and Kishinouyepenaeopsis incisa were identified as new records in Bangladesh waters. A distinguishing feature of P. pulchricaudatus is its dark brown transverse bands that do not extend to the lower half of the carapace. The identification of these species was confirmed using both morphometric characteristics and DNA barcoding techniques. Two sequences were generated for these species utilizing the 16S rRNA gene marker. The findings reveal two new records of shrimp species in Bangladesh, expanding the known diversity of shrimp in the region and highlighting the presence of previously undocumented species. Dhaka Univ. J. Biol. Sci. 33(2): 111-117, 2024 (July)